Oral Health Status and Oral Health-Related Behavior among Schoolchildren of Tumkur - Darshana Bennadi; H Mythri; J V Bharatesh (Wolters Kluwer Medknow Publications, 2022)
Background: The health of the mouth and dentition plays a major role in the life of the child and hence given the main concern with objective to assess oral health status and behavior among schoolchildren and action to be taken to maintain good oral health and behavior among schoolchildren through school oral health programs. Aim: To assess oral health status and oral health behavior among schoolchildren of Tumkur. Methodology: A cross-sectional survey was conducted among schoolchildren of Tumkur using the convenience sampling method. Oral health status was assessed using modified World Health Organization pro forma and behaviors related to oral health was assessed using a pretested questionnaire. Data were analyzed using SPSS software version 18 where descriptive statistics and Chi-square test were applied. P <0.05 was considered statistically significant Results: A total of 3641 children were included in the study from 14 randomly selected schools with the age group ranging from 6 to 16 years. Decayed tooth was observed to be more in primary (36%) as well as permanent teeth (62%) and only 30% of the children mentioned they had visited a dentist in the past 1 year and the pain was the main reason for their visit. Majority of their practice was self-relied (94%). Conclusion: Overall scenario of the children's oral health is not deplorable, care should be taken to educate them about proper brushing techniques and reduce consumption of sugar.